STUDYING THE PROCESS OF OBTAINING PHOSPHATES OF METALS BASED ON THE PHASE EQUILIBRIA OF FOUR COMPONENT SYSTEMS - Aikozova Laura Dauletbekovna; Tukibayeva Ainur Sultankhanovna; Bayeshov Abduali; Leska Boguslawa; Baiysbai Omirbek Pernebaiuly (Academic Scientific Journal of Chemistry, 2019)
In this article the literature data on phase equilibria in four-component reciprocal systems are given and the solubility in the mutual quaternary systems FeCl2-H3PO4-H2O was determined in the range of concentrations of phosphoric acid from 5 to 55% H3PO4 at temperatures of 25, 60 and 80ºС. The calculated data on the construction of the crystallization fields of salts in the studied system, taking into account the possible formation of one- and two-substituted iron phosphates, are given. The optimum consumption of phosphoric acid solution to obtain the desired product is defined. The maximum possible yield of the finished product in these conditions of the process from a unit mass of ferric chloride is also established. The consumption of phosphoric acid was determined according to the diagram according to the lever rule as the ratio of the segments BM5 and M5D. The excess acid ratio over the stoichiometric norm was calculated for the formation of monosubstituted phosphates for the FeCl2-H3PO4-H2O system